Immunosuppression Induced by Chronic Inflammation and the Progression to Oral Squamous Cell Carcinoma. (8th December 2016) - Sun, Yujuan; Liu, Nan; Guan, Xiaobing; Wu, Hongru; Sun, Zheng; Zeng, Hui
Abstract : Oral squamous cell carcinoma (OSCC) is an aggressive, invasive malignancy of epithelial origin. The progression from premalignant lesions—oral leukoplakia (OLK) and oral lichen planus (OLP)—to OSCC involves complex inflammatory processes that have not been elucidated. We investigated the roles of inflammatory mediators and infiltrating immunocytes in the pathogenic progression of OLK and OLP to OSCC. The occurrence of regulatory T-cells (Tregs) and tumor-associated macrophages (TAMs) and the expression of anti-inflammatory cytokines and proinflammatory cytokines were investigated in OLK, OLP, and OSCC tissues. Immunohistochemical staining of CD4, FOXP3, CD68, TGF- β 1, IL-10, IL-4, IFN- γ, and MCP-1 showed that the occurrence of Tregs and TAMs increased in parallel with disease progression in OLK and OSCC. IL-10 gradually increased during the early stages of OLK and in OSCC. Infiltrating IL-4 + macrophages were seen with increasing frequency in OLK tissue during the progression of oral dysplasia. Fewer TGF- β 1 + macrophages were seen in OSCC than in OLK and OLP. The expression of IFN- γ decreased gradually with the OLK development and had the lowest expression in OSCC. MCP-1 expression did not change significantly during the development of OSCC. The results suggested that the immunosuppression induced by chronic inflammation promotes tumorigenesis in OSCC, rather than initiating it.